Coaching, Touching, and False Allegations of Sexual Abuse in Canada. (April 2016) - Pépin-Gagné, Joannie; Parent, Sylvie
Whether in sports training or in physical education contexts, touching is an integral component of the coaches' tasks. However, recent evidence suggests that touching has become a significant concern for coaches in Canada and elsewhere, maybe due to the increased sensitivity toward child protection discourses. In fact, it appears that some coaches are concerned that touching children while coaching can potentially lead to false allegations of abuse by young people in their care or by the young person's parents. These apprehensions are pushing some coaches to protect themselves by adopting various strategies or by avoiding certain situations, like touching. Recent evidence suggests that fears of false allegations can represent an obstacle for the prevention of sexual abuse. Moreover, these fears can have a significant impact on the victims of these crimes. Throughout this article, we explore the question of touching in coaching and the fears of false allegations of sexual abuse sometimes associated. The authors focus on understanding the foundations of these fears and offer some answers to the difficult questions that arise from this situation from a Canadian perspective.